A new species of Tyrannomyrmex (Hymenoptera: Formicidae: Myrmicinae) from India - Borowiec, Marek L. (Zootaxa, 2007)
A second species in the myrmicine ant genus Tyrannomyrmex Fernández, 2003, T. dux sp. n., based on a solitary worker from a leaf litter sample from Kerala state, southern India, is described. The original genus definition is slightly modified to include the description of this new species.